Respostas
respondido por:
5
-2x²-16x=0
-2x(x+8)=0
-2x=0
x=0/-2
x=0
x+8=0
x=0-8
x=-8
2 valores de x 0 e -8
s={0,-8}
-2x(x+8)=0
-2x=0
x=0/-2
x=0
x+8=0
x=0-8
x=-8
2 valores de x 0 e -8
s={0,-8}
begarcia:
porque "(x+8)" ???
respondido por:
1
-2x²-16x=0
-2x(x+8)=0
-2x=0
x=0/-2
x=0
x+8=0
x=0-8
x=-8
2 valores de x 0 e -8
s={0,-8}
acho que é assim
-2x(x+8)=0
-2x=0
x=0/-2
x=0
x+8=0
x=0-8
x=-8
2 valores de x 0 e -8
s={0,-8}
acho que é assim
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás